2021
DOI: 10.1021/acs.energyfuels.1c00715
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Catalytic Conversion of Biomass-Derived Glucose to Fine Chemicals

Abstract: The energy crisis is a major challenge for the 21st century due to fossil fuel depletion. Biomass, the waste material from plants or animals containing renewable and abundant carbon resources, is considered as an ideal alternative for fossil fuels. Glucose, as a building unit of cellulose, is the most widely used monosaccharide that has wide applications ranging from pharmaceuticals and food industries. The conversion of biomassderived glucose has become a major and multidisciplinary field of research. Various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 141 publications
0
15
0
Order By: Relevance
“…Biomass is derived from plant or animal-based material that can directly be used as fuel to produce heat via combustion or electricity. [1] To satisfy the energy demand, the development of sustainable renewable energy sources is need of an hour due to the depletion of fossil fuels. [2] Also, the use of non-renewable fossil fuels increases greenhouse gas emissions and leads to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Biomass is derived from plant or animal-based material that can directly be used as fuel to produce heat via combustion or electricity. [1] To satisfy the energy demand, the development of sustainable renewable energy sources is need of an hour due to the depletion of fossil fuels. [2] Also, the use of non-renewable fossil fuels increases greenhouse gas emissions and leads to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Lignocellulose is the major component in abundant biomass resources, consisting mainly of polysaccharides (cellulose and hemicellulose) and phenolic compounds (lignin). , Cellulose (35–50%) is the main part of the overall residues and occurs together with the other components hemicellulose (20–35%) and lignin (10–25%). Various methods based on hydrothermal, chemocatalytic, or biological enzymatic techniques are known for the depolymerization of polysaccharides to their primary constituents, e.g., glucose and xylose . These sugars are readily available as starting material for the synthesis of oxygenates containing structural moieties and functionalities of furans, alcohols, and aldehydes. , For example, glucose and xylose are converted to 5-hydroxymethylfurfural (HMF) and furfural, respectively, by a simple dehydration method achieving yields of up to ∼90% over a wide range of acid–base catalysts such as zeolites, Amberlyst-15, Nafion, Sn-beta, Nb 2 O 5 , TiO 2 , CrCl 3 , etc. , Oxygenates which contain diol functionalities such as ethylene glycol (EG), 1,3-propanediol (ProDO), 1,4-butanediol (BDO), 1,5-pentanediol (PDO), and 1,6-hexanediol (HDO) are highly valued commodity chemicals, conventionally produced from fossil resources. However, recent studies have demonstrated the feasibility of diol production from renewable resources . For example, EG can be catalytically produced from cellulose .…”
Section: Introductionmentioning
confidence: 99%
“…24 Similarly, Jiang et al published a review article on the thermocatalytic conversion of biomass-derived glucose to value-added chemicals. 25 In contrast to these previous reviews, our work focuses on photocatalysts, such as metal sulfides, zeolites, TiO 2 , and g-C 3 N 4 -based porous materials, and the wide range of products that can be produced from biomass valorization. In addition, we primarily discuss photocatalytic instead of thermocatalytic systems, which are more sustainable, efficient, and environmentally benign.…”
Section: Introductionmentioning
confidence: 99%
“…In another work, Servio and co-workers focused only on photocatalytic H 2 production from biomass . Similarly, Jiang et al published a review article on the thermocatalytic conversion of biomass-derived glucose to value-added chemicals . In contrast to these previous reviews, our work focuses on photocatalysts, such as metal sulfides, zeolites, TiO 2 , and g-C 3 N 4 -based porous materials, and the wide range of products that can be produced from biomass valorization.…”
Section: Introductionmentioning
confidence: 99%